Efektivitas Peranan Auditor Internal Dalam Mewujudkan Good Corporate Governance Pada Perbankan - Wuryani, Eni; Tjiptohadi, Tjiptohadi (AKRUAL: JURNAL AKUNTANSI, 2009)
AbstractBuild the role of an effective internal auditors can not be separated from the application of good corporate governance in the company overall. The principles of Good Corporate Governance (GCG) such as fairness, independency, transparency, accountability, and responsibility in an effort to improve professionalism and the welfare of shareholders without ignoring stakeholder interest. Each report weaknesses in internal control or risk control effectiveness of the bank should be immediately followed up by the board of commissioners, board of directors, and executive officers related.